K∗(892)0 and φ(1020) production at midrapidity in pp collisions at s =8 TeV - Acharya, S.; Adamovã, D.; Adhya, S.P.; Adler, A.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; et al. (American Physical Society, 2020)
The production of ${K}^{*}{(892)}^{0}$ and $\ensuremath{\phi}(1020)$ in $pp$ collisions at $\sqrt{s}=8$ TeV was measured by using Run 1 data collected by the ALICE collaboration at the CERN Large Hadron Collider (LHC). The ${p}_{\mathrm{T}}$-differential yields ${d}^{2}N/dyd{p}_{\mathrm{T}}$ in the range $0<{p}_{\mathrm{T}}<20$ GeV/$c$ for ${K}^{*0}$ and $0.4<{p}_{\mathrm{T}}<16$ GeV/$c$ for $\ensuremath{\phi}$ have been measured at midrapidity, $|y|<0.5$. Moreover, improved measurements of the ${K}^{*0}(892)$ and $\ensuremath{\phi}(1020)$ at $\sqrt{s}=7$ TeV are presented. The collision energy dependence of ${p}_{\mathrm{T}}$ distributions, ${p}_{\mathrm{T}}$-integrated yields, and particle ratios in inelastic $pp$ collisions are examined. The results are also compared with different collision systems. The values of the particle ratios are found to be similar to those measured at other LHC energies. In $pp$ collisions a hardening of the particle spectra is observed with increasing energy, but at the same time it is also observed that the relative particle abundances are independent of the collision energy. The ${p}_{\mathrm{T}}$-differential yields of ${K}^{*0}$ and $\ensuremath{\phi}$ in $pp$ collisions at $\sqrt{s}=8$ TeV are compared with the expectations of different Monte Carlo event generators.
Keywords: Physics; Energy (signal processing); Large Hadron Collider; Atomic physics; Crystallography; Particle physics; Chemistry; https://purl.org/pe-repo/ocde/ford#1.03.00